Occupational Physical Stress Is Negatively Associated With Hippocampal Volume and Memory in Older Adults - Burzynska, Agnieszka Z.; Ganster, Daniel C.; Fanning, Jason; Salerno, Elizabeth A.; Gothe, Neha P.; Voss, Michelle W.; McAuley, Edward; Kramer, Arthur F. (Frontiers in Human Neuroscience, 2020)
Our jobs can provide intellectually and socially enriched environments but also be the source of major psychological and physical stressors. As the average full-time worker spends >8 hours at work per weekday and remains in the workforce for about 40 years, occupational experiences must be important factors in cognitive and brain aging. Therefore, we studied whether occupational complexity and stress are associated with hippocampal volume and cognitive ability in 99 cognitively normal older adults. We estimated occupational complexity, physical stress, and psychological stress using the Work Design Questionnaire (Morgeson & Humphrey 2006), Quantitative Workload Inventory and Interpersonal Conflict at Work Scale (Spector & Jex (1998). We found that physical stress, comprising physical demands and work conditions, was associated with smaller hippocampal volume and poorer memory performance. These associations were independent of age, gender, brain size, socioeconomic factors (education, income, job title), duration of the job, employment status, leisure physical activity and general stress. This suggests that physical demands at work and leisure physical activity may have largely independent and opposite effects on brain and cognitive health. Our findings highlight the importance of considering midlife occupational experiences, such as work physical stress, in understanding individual trajectories of cognitive and brain aging.